George Westinghouse papers - Westinghouse, George, 1846-1914.
Typewritten reminiscences and anecdotes about Westinghouse by individuals who knew and worked with Westinghouse. Written and collected, 1935-1937, to celebrate the 50th anniversary of the founding of the Westinghouse Electric & Manufacturing Company.
Inventor and industrialist.
Collection material in English.
Keywords: Westinghouse Electric & Manufacturing Company; Electric industries -- United States; Industrialists; Inventors